Analisis Pengembangan Media Pembelajaran Pengolah Angka (Spreadsheet) Berbasis Video Screencast - Muhammad Munir (Faculty of Engineering, Universitas Negeri Yogyakarta, 2013)
The objectives of this study were to develop Screencast-based learning media for the course of spreadsheets and to investigate its performance. This study utilised research and development approach that consists of: (1) Preparation that includes preparing the tools and materials (2) Recording that includes selecting an area of captures, recording mode screencast, and audio settings on the recording device, (3) Editing that includes adding drawing and callouts elements, editing the timeline, adding zooming effects, animation effects, and audio supports for the introduction, backsound, and narration, (4) Publishing that includes publishing the edited video into a single unit, converting the video format into mp4 with the format factory, (5) Finishing that includes making quizzes then merging the videos and quizzes into united media with the.exe extension. The performance of the media video has achieved the determined plan. When it is run, auto play menu appears to select the screencast.exe.